2016
DOI: 10.1021/acs.joc.6b01569
|View full text |Cite
|
Sign up to set email alerts
|

Red-Emitting Tetracoordinate Organoboron Chelates: Synthesis, Photophysical Properties, and Fluorescence Microscopy

Abstract: Seven tetracoordinate organoboron fluorophores with heterobiaryl N,O- or N,N-chelate ligands were prepared and photophysically characterized (in toluene). The electronic variation of the heteroaromatic moiety provided a means for the fine-tuning of the UV/vis absorption and emission spectra. In the most interesting cases, the spectra were red-shifted to maximum absorbance at wavelengths longer than 500 nm and emission maxima between 620 and 660 nm. The pronounced intramolecular charge-transfer character of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 56 publications
(128 reference statements)
1
25
0
Order By: Relevance
“…The stronger electron‐donating ‐NMe 2 shifts the emission maximum even close to 600 nm. These new BAI dyes usefully complement a previously investigated series of racemic BAI dyes with demonstrated applications in bioimaging . Further, this work provides an attractive path for the design of spectrally fine‐tuned emission of CPL‐SOM architectures …”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…The stronger electron‐donating ‐NMe 2 shifts the emission maximum even close to 600 nm. These new BAI dyes usefully complement a previously investigated series of racemic BAI dyes with demonstrated applications in bioimaging . Further, this work provides an attractive path for the design of spectrally fine‐tuned emission of CPL‐SOM architectures …”
Section: Introductionmentioning
confidence: 78%
“…Much effort has been dedicated to the development of synthetically flexible platforms which enable the photophysical fine‐tuning of the dyes . As part of our own research program we have developed borylated arylisoquinoline (BAI) dyes, which in their N,C‐chelate variant are strongly emitting, solvatochromic, and two‐photon‐absorbing charge‐transfer fluorophores with application potential in bioimaging . With the idea to further enrich the photophysics of this fascinating platform we have built on their biaryl structure, which provides a means to arrive at dyes with helical chirality and the corresponding observation of interesting chiroptical properties, including the detection of circularly polarized luminescence (CPL) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As part of our research program we have been interested in arylisoquinolines as chelate ligands for organoboron dyes (BAI dyes) with specific focus on their appropriateness for bioimaging with confocal or multiphoton fluorescence microscopy . In a recent work we have demonstrated that four‐coordinate N,C‐chelate dyes such as the ones shown in Figure (dye 1 – 4 ) are interesting candidates for these applications .…”
Section: Introductionmentioning
confidence: 99%